The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/hbm.25824
|View full text |Cite
|
Sign up to set email alerts
|

The causal role of the bilateral ventrolateral prefrontal cortices on emotion regulation of social feedback

Abstract: The ventrolateral prefrontal cortices (VLPFC) are crucial regions involved in voluntary emotion regulation. However, the lateralization of the VLPFC in downregulating negative emotions remains unclear; and whether the causal role of the VLPFC is generalizable to upregulating positive emotions is unexplored. This study used transcranial magnetic stimulation (TMS) to examine the causal relationship between the left/right VLPFC and social emotion reappraisal. One hundred and twenty participants were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 95 publications
1
20
0
Order By: Relevance
“…Of these, 19 studies fulfilled the eligibility criteria. Amongst them, we did not receive a response from the corresponding author about the missing data in one study [ 43 ], and the authors of other study were unable to provide data until three months later due to isolation [ 69 ]. Finally, 17 studies were included in the meta-analysis [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 19 studies fulfilled the eligibility criteria. Amongst them, we did not receive a response from the corresponding author about the missing data in one study [ 43 ], and the authors of other study were unable to provide data until three months later due to isolation [ 69 ]. Finally, 17 studies were included in the meta-analysis [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested the association between activation of rVLPFC and self-reported negative emotions (Eisenberger et al, 2003;Phan et al, 2005;Masten et al, 2009), as well as reappraisal success (Wager et al, 2008). Also, a previous study in our laboratory has provided causal evidence to support the critical role of the rVLPFC in reappraisal outcome (He Z. et al, 2018;He et al, 2020a,b;Li et al, 2022). It is well-known that the rVLPFC is an essential region in the inhibition process (Aron et al, 2004;Leung and Cai, 2007;Levy and Wagner, 2011;Rae et al, 2015;Apšvalka et al, 2022), which is usually observed in the Go/No-go, Think/No-think, and Stop Signal tasks (refer to meta-analysis by Levy and Wagner (2011), Apšvalka et al (2022)).…”
Section: Discussionmentioning
confidence: 87%
“…and regulatory goals (up-or downregulation; Ochsner et al, 2012;Kohn et al, 2014;Morawetz et al, 2017). Previous studies in our laboratory by transcranial magnetic stimulation (TMS) have further demonstrated that the VLPFC is an essential brain region in reappraisal (He et al, 2020b;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Location of the coil was based on the International 10/20 electroencephalogram system. The rVLPFC is at the F8 and the vertex is at the Cz (Li et al, 2022; Zhao et al, 2021). The resting motor threshold (rMT) of each participant was measured in the motor cortex (the C3) and the threshold was defined as 50% of the pulses that reliably produced thumb twitch.…”
Section: Methodsmentioning
confidence: 99%
“…To fill this gap, our lab implemented a series of studies that used an explicit cognitive reappraisal task to explore the role of the rVLPFC on voluntary down‐regulation of social pain. These studies supposed to facilitate the rVLPFC by using the anodal tDCS (He et al, 2018; He, Liu, et al, 2020) or high‐frequency repetitive transcranial magnetic stimulation (rTMS) (He, Zhao, et al, 2020; Li et al, 2022; Zhao et al, 2021), which found that the participants in active tDCS/rTMS group performed better in reappraising social pain compared with the sham tDCS/rTMS group.…”
Section: Introductionmentioning
confidence: 99%